2022
DOI: 10.1111/jocs.16852
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of total arch replacement versus proximal aortic replacement in acute type A aortic dissection: Meta‐analysis of Kaplan–Meier‐derived individual patient data

Abstract: Objectives: To evaluate the long-term outcomes of a conservative approach (with proximal aortic replacement with or without hemiarch replacement) versus an aggressive approach (with total aortic arch replacement) in the treatment of acute type A aortic dissection (ATAAD).Methods: We performed a pooled analysis of Kaplan-Meier-derived individual patient data from studies with follow-up comparing the aforementioned approaches to treat patients with ATAAD.Results: Eighteen studies met our eligibility criteria, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Several cohort studies have compared PAR and TAR for ATAAD, with the majority of results aligning with those of Sa et al 2 suggesting TAR's superiority over PAR (with or without hemiarch). In the 14‐year study of 213 ATAAD patients by Vendramin et al, 3 Group 1 consisted of 138 patients who underwent PAR while Group 2 included 75 TAR patients.…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…Several cohort studies have compared PAR and TAR for ATAAD, with the majority of results aligning with those of Sa et al 2 suggesting TAR's superiority over PAR (with or without hemiarch). In the 14‐year study of 213 ATAAD patients by Vendramin et al, 3 Group 1 consisted of 138 patients who underwent PAR while Group 2 included 75 TAR patients.…”
mentioning
confidence: 53%
“…The authors concluded that TAR seems to be the more favorable approach for treating ATAAD due to improved long-term survival and lower risk of need of reoperation. 2 Several cohort studies have compared PAR and TAR for ATAAD, with the majority of results aligning with those of Sa et al 2 suggesting TAR's superiority over PAR (with or without hemiarch). In the 14-year study of 213 ATAAD patients by Vendramin et al, 3 Group 1 consisted of 138 patients who underwent PAR while Group 2 included 75 TAR patients.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…In this context, Tirone-David expresses concerns that aortic arch replacement is not appropriate for the “general cardiac surgeon” ( 6 ). On the other hand, it has to be taken into account that Sa et als' meta-analysis demonstrated that an aggressive approach seems to confer better long-term survival and lower risk for reoperation in the follow-up of patients treated for ATAAD ( 7 ). Following these considerations, many new surgical techniques, perfusion strategies, and graft devices have been introduced in the last few years: from ABO perfusion strategy to normothermic frozen elephant trunk surgery without circulatory arrest, and from new FET graft devices to different types of HAR.…”
mentioning
confidence: 99%